Career Concerns, Inaction, and Market Inefficiency: Evidence from Utility Regulation - Severin Borenstein; Meghan Busse; Ryan Kellogg (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2010)
This paper examines how career concerns can generate inefficiencies not only within firms but also in market outcomes. Career concerns may lead agents to avoid actions that, while value-increasing in expectation, could potentially be directly associated with a bad outcome. We apply this theory to natural gas procurement by regulated public utilities and show that career concerns may lead to a reduction in surplus-increasing market transactions during periods when the benefits of trade are likely to be greatest. We show that data from natural gas markets are consistent with this prediction and difficult to explain using alternative theories.
Keywords: 330